GAMBARAN PASIEN KARSINOMA TIROID BERDIFERENSIASI DI RSUP SANGLAH TAHUN 2015-2020 - Wisescistiati, Made Visvayoni; Yuniawaty Wetan, Ni Gusti Ayu Agung Manik; Manuaba, Ida Bagus Tjakra Wibawa; Adiputra, Putu Anda Tusta (E-Jurnal Medika Udayana; Vol 11 No 4 (2022): E-Jurnal Medika Udayana, 2022)
ABSTRACT Background: differentiated thyroid carcinoma (DTC) is the most common type found in thyroid malignancies. Onset of the disease is influenced by several factors such as history of radiation exposure, environmental influences and iodine intake in certain areas. Due to the limited data in Indonesia related to the mapping of differentiated thyroid cancer cases, the author is interested in conducting this study. Objective: to determine the description of differentiated thyroid carcinoma patients in Sanglah General Hospital year 2015-2020. Methods: cross-sectional descriptive study. The population and samples were all patients diagnosed with differentiated thyroid cancer treated at the SMF/Surgery Department of Sanglah General Hospital year 2015 -2020. The variables in this study are age, gender, area of residence, main diagnosis, staging and therapy. Results: total sample obtained 223 patients. Most common age group were 41-50 years old with 52 people (23.3%). Women are more common with 173 people (77.6%). Denpasar City has the highest number of cases with 75 people (33.6%). The main diagnosis is papillary thyroid cancer (PTC) with 215 cases (96.4%). Stage I are most found with 140 cases (62.8%). Most widely given therapy is total thyroidectomy in 183 people (82.1%) and 124 people (55.6%) received radio ablation. Conclusion: In this study, differentiated thyroid carcinoma was mostly found in women, at the age of 41-50 years, residents living in Denpasar. Papillary thyroid cancer (PTC) as the most common type in stage I and mostly treated with total thyroidectomy. Keywords : description, differentiated thyroid carcinoma, sociodemographic